PROMISING DIRECTIONS OF AGRICULTURAL PRODUCTION IN UZBEKISTAN (American Journal of Interdisciplinary Research and Development, 2025)
The article discusses promising areas of agricultural production in Uzbekistan. One of the promising areas of agricultural production is the implementation of comprehensive work on the creation of environmentally friendly agricultural products.